2004
DOI: 10.1080/10284150400019922
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Solitary Tract Nucleus of the Rat Following Perinatal Food Restriction and Subsequent Nutritional Rehabilitation

Abstract: Newborn of altricial species maintain functional gustatory communication with the mother because the neural substrate and the capacity to discriminate and promote gustofacial responses are already operating. Because little is known about the effects of perinatal food restriction upon gustatory neuronal brain stem structures, we characterized neuronal Golgi-Cox alterations of the solitary tract rostral portion (NSTr) where gustatory information is known to convey in neonatal Wistar rats. Pre-and neonatally unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
5
20
0
1
Order By: Relevance
“…The finding of significant reductions in body and brain weights concurrent with ear-and-eye-opening delays throughout the study is in line with previous reports showing that different perinatal underfeeding paradigms consistently interfere with food intake, physical growth, low emission of vocalizations and poor maternal care and delayed sensory maturation, particularly in the olfactory channel when the mother-litter bonds are at a critical stage and are essential for the pups' survival and brain growth (Salas et al 1970, Math and Davrainville 1980, Salas et al 1984, Almli et al 1985, Alberts and Cramer 1988, Diaz-Cintra et al 1994, Fleming et al 1999, Torrero et al 2000, Tonkiss et al 2003, Rubio et al 2004). …”
Section: Physical Developmentsupporting
confidence: 88%
“…The finding of significant reductions in body and brain weights concurrent with ear-and-eye-opening delays throughout the study is in line with previous reports showing that different perinatal underfeeding paradigms consistently interfere with food intake, physical growth, low emission of vocalizations and poor maternal care and delayed sensory maturation, particularly in the olfactory channel when the mother-litter bonds are at a critical stage and are essential for the pups' survival and brain growth (Salas et al 1970, Math and Davrainville 1980, Salas et al 1984, Almli et al 1985, Alberts and Cramer 1988, Diaz-Cintra et al 1994, Fleming et al 1999, Torrero et al 2000, Tonkiss et al 2003, Rubio et al 2004). …”
Section: Physical Developmentsupporting
confidence: 88%
“…The GFR alterations in response to tastants found in the present study are in line with neuronal hypoplasia and the disorganization of the dendritic tree and spines observed along the relay nuclei of the gustatory and motor facial nucleus [7,13,15,36,37]. In this regard, it is known that descending input from the insular cortex, lateral hypothalamus, and central amygdale modulate the brainstem sensory and motor mechanisms of the newborn to produce fluid and food intake, nipple attachment, and the GFR integration that seems to be disrupted in the UG animals studied here [19,[38][39][40][41].…”
Section: Discussionsupporting
confidence: 63%
“…In the past, a number of studies have shown that perinatal undernutrition in the rat delays the maturation of sensory systems and causes the expression of altered motor patterns; these effects lead to a significant deficiency of somatosensory, auditory, visual, and chemosensory stimulation that may be essential for long-term behavioral performance [1][2][3][4][5][6][7][8]. Perinatal undernutrition mainly interferes with the anatomical organization of central nervous system (CNS) areas which undergo a phase of postnatal cell proliferation; these areas include the cerebral and cerebellar cortices, the hippocampus, central amygdaloid nucleus, olfactory bulb, and solitary tract nucleus, and they participate in the head movements, mouth opening and closing, chewing, food ingestion, and chemosensory CNS integration [8,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After birth, CG rats were fed by interchanging a pair of normally lactating dams every 12 h between litters as previously described. 47 This experimental procedure allows adequate nursing of pups and the care given by the mother (body licking, retrieving, thermal and tactile stimulation when crouching, anogenital stimulation, etc.) when the dams were interchanged between litters.…”
Section: Control Group (Cg)mentioning
confidence: 99%